Fatores ambientais de crianças e adolescentes com paralisia cerebral atendidos pelo serviço de fisioterapia pediátrica de uma universidade do interior do Amazonas - Silva, Olívia Maria dos Santos (Brasil, 2025)
Objective: to characterize the environmental factors of children and adolescents with cerebral palsy (CP) at a physiotherapy outpatient clinic of a university in the interior of Amazonas state. Methods: This is a descriptive, retrospective study based on medical records. The study included children and adolescents aged between zero and 18 years who were assessed by the pediatric physiotherapy department at the Institute of Health and Biotechnology (ISB) in 2022 and the first half of 2023. Patients with missing data, outside the established period, and medical records of the same patient from different periods were excluded. There were nine losses and 17 patients made up the final sample. The data was subjected to descriptive analysis using Jamovi software, version 1.6.23.0. Results: the majority of participants, around 11 (64.7%), were male. A number of 8 (47.1%) participants had bilateral spastic cerebral palsy, 8 (47.1%) had level V on the Gross Motor Function Classification System (GMFCS) and 5 (29.4%) level I and IV on the Manual Ability Classification System (MACS). In terms of environmental factors, the biggest barriers identified in this study were not receiving social aid and/or benefits, in a total of 9 (52.9%) participants; low family income, around 8 (47.1%); lack of adequate medical follow-up, with 11 (64.7%) participants not having access to a pediatrician and 12 (70.6%) to a neurologist; lack of walking and mobility aids, around 12 (70.6%) individuals. Conclusion: the results point to the presence of numerous barriers in health, education and care services, in the consumption and use of products and technologies for personal use that impact on the functionality and development of these individuals. The findings point to the need for a greater understanding of the other environmental factors that involve these individuals in the context in which they find themselves, in order to contribute to the planning of health actions and services that impact on the development and quality of life of these children and adolescents.